Morphometric characteristics of red crab (Thalamita spinimana) in Dompak Tanjungpinang Waters, Riau Islands - Aprilya Triana; Wahyu Muzammil; Dedy Kurniawan; Susiana Susiana (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2022)
The morphometric characteristics of the red crab (Thalamita spinimana) have not been widely studied. This research was conducted from March to May 2021 in the waters of Dompak Tanjungpinang, Riau Islands. Each sample obtained directly measured the morphometric part using a caliper or calipers with an accuracy of 0.05 mm and the crab body weight was also weighed using a digital scale with an accuracy of 0.1 g. The samples obtained during the study were 119 crabs, of which 84 female red crabs and 35 male red crabs. The carapace width range for female crabs is 55.40 – 88.32 mm, while in male crabs the carapace width range is 16.35 and 34 individuals 68.96 – 90.94 mm. The weight of female red crabs is in the range of 50.0 – 103.6 g, while the weight of male crabs is in the range of 49.0 – 142.8 g.